Exploring the effects of spatial distance on public perception of waste-to-energy incineration projects. (15th April 2022) - Zhou, Qianqian; Xu, Min; Liu, Yong; Cui, Caiyun; Xia, Bo; Ke, Yongjian; Skitmore, Martin
Graphical abstract: Highlights: Spatial distance affects public perception of waste-to-energy incinerators. Impact of spatial distance on perceived risk perception shows the marginal zone effect. Effect of spatial distance on other public perception conforms to the ripple effect. The findings will help environmental psychologies related to potentially hazardous facilities. Abstract: The spatial distance of residents from potentially harmful facilities plays a vital role in shaping their perceptions of the facilities. Based on environmental psychology theories, such as the ripple effect, psychological typhoon eye effect, and marginal zone effect, two waste-to-energy (WTE) incineration plants in China's Zhejiang province are used as case studies to understand peoples' perceptions. Following a questionnaire survey of local residents, the results of a one-way ANOVA indicate a low acceptance of incinerators and a high level of perceived risk; the impact of spatial distance on the local residents' level of perceived risk correspond to the marginal zone effect; and the perception of economic benefits, trust, fairness, and acceptance of WTE incinerators have a ripple effect. Furthermore, the impact of spatial distance is effectively eliminated or alleviated by a range of community engagement approvals and various forms of economic compensation. These findings enrich the knowledge system related to environmental psychology research on NIMBY infrastructure projects and contribute toward better understanding of public psychology in order to provide a future reference for more efficient decision-making models.